Properties Aspal Akibat Substitusi Getah Karet Dengan Filler Abu Arang Tempurung Kelapa - Budiati, Anik; Dewi, Fillia Indah Kumala; Alwi, Mukhammad Khafid Zakiya; Fajrinia, Citto Pacama (Fakultas Teknik Universitas Bhayangkara Surabaya, 2025)
The use of additives originating from nature in the form of latex (rubber latex) and charcoal ash from coconut shells is expected to be a solution in improving the quality of road pavement. Latex (rubber latex) substitution of 1%, 2% and 3% and charcoal ash of 1%; 1.5%; and 2% were used in this research, with the aim of determining the effect of additives on asphalt properties values based on the 2018 Bina Marga Specifications. In the penetration test there was a decrease with an optimum substitution of 59.1 at a proportion of 2% latex and 1.5% charcoal ash. . In flash point and burn point tests, the addition of latex and charcoal ash caused the asphalt to heat up more quickly at lower temperatures than asphalt without additional ingredients. In testing the flash point and burning point, the optimum substitution was 1% latex and 1.5% charcoal ash. Meanwhile, in the ductility test, with the substitution of 1% latex and 1.5% charcoal ash, a ductility value of 105 mm was obtained. From several tests, it was concluded that the optimum substitution was for the 2% latex variant and 1.5% charcoal ash. These results meet the 2018 Bina Marga Specifications